1994
DOI: 10.1017/s0043174500080280
|View full text |Cite
|
Sign up to set email alerts
|

Perennial Weed Populations After 14 Years of Variable Tillage and Cropping Practices

Abstract: Management of perennial weeds is a major concern in reduced-tillage cropping systems. Field research was conducted at Nashua, IA, from 1977 through 1990 to evaluate the long-term impacts of tillage and cropping patterns on perennial weed populations in corn and soybean production. Continuous corn and a corn/soybean rotation were conducted utilizing moldboard plow, chisel plow, ridge tillage, and no-tillage systems. The research area was free of established perennial weed species at the initiation of the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 9 publications
3
83
0
2
Order By: Relevance
“…These field reports also pointed to the main short-coming of the simulation-based method, i.e., FlorSys only considers annual weed species. This is not a problem in tillagebased systems as shown by the evaluation (Colbach et al, 2015, submitted) but certainly leads to underestimating weed harmfulness in no-till systems which tend to favor perennials (Buhler et al, 1994;Tørresen et al, 2003;Norsworthy, 2008;Trichard et al, 2013), indicating that the low or no-till strategies identified here as optimal for reconciling production and biodiversity would only remain efficient if there were no risk perennials. Pending the development of a perennial weed dynamics model, an indicator of perennial weed spread depending on cultural practices could be developed from expert opinion.…”
Section: A Methods Producing Realistic Resultsmentioning
confidence: 85%
“…These field reports also pointed to the main short-coming of the simulation-based method, i.e., FlorSys only considers annual weed species. This is not a problem in tillagebased systems as shown by the evaluation (Colbach et al, 2015, submitted) but certainly leads to underestimating weed harmfulness in no-till systems which tend to favor perennials (Buhler et al, 1994;Tørresen et al, 2003;Norsworthy, 2008;Trichard et al, 2013), indicating that the low or no-till strategies identified here as optimal for reconciling production and biodiversity would only remain efficient if there were no risk perennials. Pending the development of a perennial weed dynamics model, an indicator of perennial weed spread depending on cultural practices could be developed from expert opinion.…”
Section: A Methods Producing Realistic Resultsmentioning
confidence: 85%
“…Several studies have documented that NT increased the density of perennial weeds (Buhler et al, 1994;Bryson and Hanks, 2001;Torresen and Skuterud, 2002). In contrast, Derksen et al (1993) concluded from several experiments that an increased association of perennial and annual grasses did not generally occur.…”
Section: Weed Community Heterogeneitymentioning
confidence: 98%
“…Efficient weed management has been identified as a limiting factor in the adoption of CT systems (Buhler et al, 1994;Stevenson et al, 1998;Mas and Verdu, 2003), as under noninversion tillage systems weed seeds are not buried when soil is inverted by the plough (Morris et al, 2010). Other than weed menace, the problems associated with the maintenance of crop residues in the field; in countries where there are alternate uses for the crop residues is also a serious concern.…”
Section: Growth and Concerns In Ca Worldwidementioning
confidence: 99%
See 2 more Smart Citations